Lactation stability of Flegfix Simmental cows with different genotypes in the conditions of Uzbekistan - Shakirov Kakhramon; Soatov Utkir; Shayusupov Bobir; Otaganov Ibrokhim; Akhmedov Khurshid (BIO Web of Conferences)
The article presents the results obtained in the studies conducted in the Flegfix Simmental cows of different genotypes brought to the Republic from abroad. In the studies, the indicators of milk yield of cows were studied. In group I, 20% purebred Holstein and 80% purebred Simmental, obtained from crossbreeding with Red-Ola Holstein, were selected in groups II and III of pure breed Flegfix Simmental (Red-Ola). The milk yield of cows in the first lactation was studied in the natural climate, storage and feeding technological conditions of the imported cows of Uzbekistan.